2006
DOI: 10.1002/app.24135
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic, thermal, and electrical investigations of PVDF films filled with BiCl3

Abstract: Poly(vinylidene fluoride) (PVDF) films filled with BiCl 3 in the mass fraction range of 0.1 W 10 were prepared. a-and b-Crystalline PVDF phases were detected and characterized by spectroscopic analysis. Fourier transform infrared analysis detected the presence of a-and bphase head-to-head and tail-to-tail polymer chain defects. The band detected at 1670 cm À1 was assigned to C¼ ¼C, indicating polarons in the polymeric matrix. The degree of crystallinity increased by increasing the filling level (FL), and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…The infrared characteristic band frequencies are given in Table 1 along with their sources of origin. It was observed that the characteristic bands are almost independent of the film thickness and are in conformity with the results obtained by other groups [5,[18][19][20][21][22][23][24][25]. The authors have assigned frequencies 1174, 1167, and 1181 cm −1 corresponding to 9, 12, and 20 μm pristine films, respectively, as CF 2 asymmetric stretching mode, as the CF 2 group absorbs strongly in the region 1120-1350 cm −1 .…”
Section: Pristine and Irradiated Pvdfsupporting
confidence: 90%
“…The infrared characteristic band frequencies are given in Table 1 along with their sources of origin. It was observed that the characteristic bands are almost independent of the film thickness and are in conformity with the results obtained by other groups [5,[18][19][20][21][22][23][24][25]. The authors have assigned frequencies 1174, 1167, and 1181 cm −1 corresponding to 9, 12, and 20 μm pristine films, respectively, as CF 2 asymmetric stretching mode, as the CF 2 group absorbs strongly in the region 1120-1350 cm −1 .…”
Section: Pristine and Irradiated Pvdfsupporting
confidence: 90%
“…Recent investigations of our research group revealed that the metal halide fillers modify significantly the structure and physical properties of PVDF films [10][11][12]. NaCl is known as an active solvent [13] for some polymers which can be used to form blends with PVDF.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a variety of experimental techniques were investigated to induce the formation of the β ‐phase through either modifying the conventional solution‐ and melt‐processing methods with specialized conditions (e.g., epitaxial growth from the solution on alkali halide substrates4) and additional treatments (e.g., subjecting the conventionally prepared films to mechanical stretching,5 electrical poling,6 ultra‐fast quenching,7 crystallization under high pressure,8 etc.) or by incorporating some additives (e.g., metal,9 metal halides,10 and organically modified silicates,11 etc. ).…”
Section: Introductionmentioning
confidence: 99%